Evaluation of Commercial Disinfectants Against Bacterial Pathogens Isolated from Broiler Farms - Soliman, Essam S.; Sobeih, Mohamed A.A.; Ahmad, Z. H.; Hussein, M.M.; Moneim, H.A.A. (International Journal of Poultry Science, 2009)
Five disinfectants [TH4® (combination of quaternary ammonium compounds and gluteraldhyde), Microzal® (combination of quaternary ammonium compounds and gluteraldhyde), Incospect IC 22XA (combination of quaternary ammonium compounds, gluteraldhyde and formalin), Povidone Iodine® (iodophore) and Formalin® (commercial formaldehyde 37%) were tested in a laboratory trials against four bacterial isolates (Staphylococcus aureus, Escherchia coli, Klebsiella oxytoca and Pseudomonas aureuginosa) at concentration of ( 105) isolated during epidemiological surveillance. The trials were carried in the presence and absence of organic matter (dried yeast 5%) using MIC use-dilution test. Minutely samples were collected for the bacterial counts. In the absence of organic matter, TH4® achieved the 100% killing efficacy against Staphylococcus aureus, Escherchia coli, Klebsiella oxytoca and Pseudomonas aureuginosa after 5, 5, 10 and 5 min (p<0.0001) respectively, Microzal® and Incospect IC 22XA achieved the 100% killing efficacy against the four Micro-organisms after 5 min (p<0.0001), Povidone Iodine® achieved the 100% killing efficacy after 5, 5, 5 and 10 min (p<0.0001) respectively and Formalin® achieved the 100% killing efficacy after 5, 5, 5 and 20 min (p<0.0001) respectively. In the presence of organic matter, TH4® achieved the 100% killing efficacy against Staphylococcus aureus, Escherchia coli, Klebsiella oxytoca and Pseudomonas aureuginosa after 10, 5, 20 and 20 min (p<0.0001) respectively, Microzal® achieved the 100% killing efficacy after 5, 5, 5 and 10 min (p<0.0001) respectively, Incospect IC 22XA achieved the 100% killing efficacy after 5, 5, 10 and 5 min (p<0.0001) respectively, Povidone Iodine® achieved the 100% killing efficacy against the four micro-organisms after 30 min (p<0.0001) and Formalin® achieved the 100% killing efficacy after 30, 5, 20 and 20 min (p<0.0001) respectively. The results revealed that quaternary ammonium-gluteraldhyde combination (TH4®, Microzal® and Incospect IC 22XA) although they are not proven to be environmentally safe; they are the most powerful disinfectants because of the synergistic action of the quaternary ammonium and gluteraldhyde bases.